Analisis Tingkat Kesehatan Bank Dengan Menggunakan Pendekatan RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) (Studi pada PT. Bank Mandiri, Tbk Periode 2011-2013) - Novanda Anggra Pratiwi; Adri Putra Nugraha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to determine the health of PT. Bank Mandiri Tbk in the period 2011-2013 that was measured by using RGEC approach (Risk Profile, Good Corporate Governance, Earnings, Capital). This research is quantitative descriptive research that using secondary data. The results of this study showed that the condition of PT. Bank Mandiri, Tbk is generally healthy, although there are some assessment aspects that are still in fairly good health level. Risk Profile on credit risk aspects, as measured by NPL ratio showed good condition, and market risk aspects as measured by IRR ratio also showed fairly good condition, and liquidity aspects as measured by LDR, LAR, and CR showed good condition. Good Corporate Governance consists of 11 assessment aspects that the total value of the composite are categorized as good. Earnings were measured by using ROA and NIM, this two ratios showed a high profitability level and are categorized in excellent condition. Capital were measured by CAR, the value of this ratio hang on excellent condition. The healthy condition reflects that the bank is able to manage its management properly, so it can support the development of its business and can anticipate the changes in economic conditions and banking industry. Keywords: bank health level, RGEC approach.